A water-transparent and anti-fog porous ceramic and its preparation method
By using silicon sol and a variety of solvents in porous ceramics, combined with integrity control agents, porosity enhancers and gel promoters, the contradiction between strength and transparency of porous ceramics is solved, and high strength and high porosity are achieved It has a water-transparent and anti-fog porous ceramic with adjustable transparency, which has heat insulation and anti-fog functions, and is suitable for high humidity environments.
Patent Information
- Application Number
- CN202311045980.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-18
AI Technical Summary
The existing porous ceramics are difficult to balance between strength and transparency, and lack heat insulation and anti-fog functions, especially in high-temperature and high-humidity environments, and are difficult to meet the needs of breathability, anti-fog, heat insulation and transparency adjustment.
Silicone sol is used as raw material, combined with integrity control agent, porosity enhancer and gel promoter, and through reasonable proportioning and preparation methods, water-induced transparent and anti-fog porous ceramics are prepared to achieve high strength, high porosity and The transparency is adjustable, while providing thermal insulation and anti-fog properties.
The structural integrity, transparency and strength of porous ceramics are achieved, and the heat insulation and anti-fog functions are provided in high humidity environments. The sintering temperature is low to reduce energy consumption, and the transparency and compressive strength reach 45.5% to 50.2% and 15.3. ~23.7MPa, suitable for high transparency materials and thermal insulation and anti-fog applications.
Smart Images

Figure CN116947469B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous ceramics, and in particular to a water-transparent and anti-fog porous ceramic and a preparation method thereof. Background Art
[0002] Transparent materials play an important role in the human environment. The most widely used transparent materials include organic materials and inorganic materials. Generally, transparent organic materials have poor temperature resistance and weather resistance, which affects their transparency. On the contrary, transparent inorganic materials represented by transparent ceramics or transparent glass have the advantages of high temperature resistance, high strength and good weather resistance and are used in many fields. As for the transparency adjustment of transparent glass and transparent ceramics, the former can be obtained by adding photochromic materials to it. According to the color change mechanism, it is mainly divided into photochromic glass, thermochromic glass, electrochromic glass and mechanochromic glass. For transparent ceramics, although there are many studies on its transparency, there is almost no research on the continuous adjustment of its transparency.
[0003] Regarding the strength, transparency and porosity of two typical inorganic materials, although transparent glass has good strength and transparency, there are no reports on transparent porous glass. Transparent porous ceramics have been reported, but they are mainly represented by silica-based ceramic aerogels. Although this type of aerogel has porosity and transparency, their strength is generally low. In some high temperature and high humidity environments such as bathrooms, there is an urgent need for a porous ceramic that is breathable, anti-fog, heat-insulating and has adjustable transparency. In summary, the preparation of transparent porous ceramics with high strength is still challenging. Summary of the invention
[0004] In view of the above analysis, the present invention aims to provide a water-transparent and anti-fog porous ceramic and a preparation method thereof, so as to solve one of the following technical problems: (1) the existing porous ceramics have no transparency, or have poor transparency, or have good transparency but low strength; (2) the transparency of the existing porous ceramics is difficult to continuously adjust; (3) the existing transparent inorganic materials do not have heat insulation and anti-fog functions.
[0005] The purpose of the present invention is mainly achieved through the following technical solutions:
[0006] On the one hand, the present invention provides a water-transparent and anti-fog porous ceramic, the raw materials of which include silica sol, integrity control agent, porosity enhancer and gel promoter.
[0007] Further, the integrity control agent includes one or more of propylene oxide, ethylene glycol and methylene chloride.
[0008] Furthermore, the porosity enhancing agent includes one or more of dimethylformamide, acetone, propionaldehyde and ammonia water.
[0009] Furthermore, the gel accelerator includes one or more of n-hexane, acetonitrile, methyl formate and cyclohexane.
[0010] Furthermore, the molar ratio of silica sol, integrity control agent, porosity enhancer and gel promoter is 1:(0.3-2.1):(0.05-0.8):(0.2-1.5).
[0011] The present invention also provides a method for preparing the water-transparent and anti-fog porous ceramic, comprising:
[0012] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0013] Step 2: Prepare the green body: inject the slurry into the mold and remove the bubbles in the slurry;
[0014] Step 3, green body drying and demoulding: put the mold in step 2 into an oven for drying, and take the green body out of the mold after it is dry;
[0015] Step 4: Sintering: Sintering the taken-out green body to obtain water-transparent and anti-fog porous ceramics.
[0016] Furthermore, in step 2, the bubbles in the slurry are removed by vacuum degassing, vibration degassing or centrifugal degassing.
[0017] Furthermore, in step 3, the oven is controlled to be in a non-blowing state.
[0018] Furthermore, in step 3, the drying temperature is controlled to be 30-80°C.
[0019] Furthermore, in step 4, the sintering temperature is controlled to be 500-800° C. and kept warm for 1-3 hours.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] The water-transparent and anti-fog porous ceramics of the present invention use silica sol as a raw material, to which solvents such as an integrity control agent, a porosity enhancer and a gel promoter are added. By reasonably selecting and proportioning these raw materials, it is ensured that the water-transparent and anti-fog porous ceramics of the present invention have the functions of high strength, high porosity and adjustable transparency, and at the same time have the functions of heat insulation and anti-fog.
[0022] In the preparation method of the water-transparent and anti-fog porous ceramic of the present invention, the sintering temperature is low, which greatly reduces the energy consumption.
[0023] In the preparation method of the water-transparent and anti-fog porous ceramic of the present invention, the temperature and time are precisely controlled during the sintering process to avoid devitrification of the porous ceramic, and finally obtain a structurally complete, water-transparent and anti-fog porous ceramic.
[0024] The porosity of the water-transparent and anti-fog porous ceramic of the present invention is 45.5% to 50.2%, the transparency after drying is 0.5% to 7%, the transparency after firing is 23% to 42%, the transparency after immersion in water is 55% to 82%, and the compressive strength is 15.3 to 23.7 MPa. The prepared porous ceramic has high strength, high porosity, adjustable transparency, and has both heat insulation and anti-fog functions.
[0025] The invention uses silica sol and multiple solvents to prepare a water-induced transparent and anti-fogging silicon oxide porous ceramic at low temperature, thereby achieving the coexistence of the contradictory porosity, transparency and strength of the porous ceramic.
[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents pointed out in the embodiments of the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only for the purpose of illustrating particular embodiments and are not to be construed as limiting the invention.
[0028] Figure 1 This is an optical image of the water-transparent and anti-fog porous ceramic after drying and sintering in Example 1 of the present invention;
[0029] Figure 2 This is an optical image of the water-transparent and anti-fog porous ceramic after absorbing water in Example 1 of the present invention;
[0030] Figure 3 This is a scanning electron microscope image of the water-transparent and anti-fog porous ceramic of Example 2 of the present invention;
[0031] Figure 4 This is an anti-fog diagram of the water-transparent and anti-fog porous ceramic of Example 1 of the present invention;
[0032] Figure 5 This is a heat insulation diagram of the water-transparent and anti-fog porous ceramic of Example 1 of the present invention;
[0033] Figure 6 This is a schematic diagram of the fragmentation after air blast drying of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0035] The invention provides a water-transparent and anti-fog porous ceramic. The raw materials of the water-transparent and anti-fog porous ceramic include silica sol, an integrity control agent, a porosity enhancer and a gel accelerator.
[0036] Specifically, the silica sol used may be commercially available alkaline silica sol.
[0037] Specifically, the integrity control agent includes one or more of propylene oxide, ethylene glycol and methylene chloride.
[0038] Specifically, the porosity enhancing agent includes one or more of dimethylformamide, acetone, propionaldehyde and ammonia water.
[0039] Specifically, the gel accelerator includes one or more of n-hexane, acetonitrile, methyl formate and cyclohexane.
[0040] Specifically, considering that too little integrity control agent will cause cracks to form inside the green body during drying or sintering, resulting in stress concentration and eventual fracture, which will reduce the strength of the green body and affect the final performance. However, adding too much integrity control agent will form a large number of micropores between the ceramic particles, which will cause cracks in the green body, enhance the reflection and scattering of light, and reduce the strength and transparency after sintering. Therefore, the molar ratio of silica sol to integrity control agent is controlled to be: 1: (0.3~2.1).
[0041] Specifically, considering that too little porosity enhancer will increase the density of the green body and reduce the pores, while too much will lead to excessive pore formation, reduce the density of the ceramic, reduce the mechanical strength, and increase the refraction and scattering of light, resulting in reduced transparency. Therefore, the molar ratio of silica sol to porosity enhancer is controlled to be: 1: (0.05-0.8).
[0042] Specifically, considering that too little gel accelerator leads to prolonged gelation time or even no gelation, reduced uniformity of the internal structure of the gel, a large number of defects, making it easier to break, and reduced mechanical properties; however, too much gel accelerator makes the gelation speed too fast, reduces density, increases the internal stress of the gel, and cracks are prone to appear during drying and sintering, resulting in reduced transparency and mechanical properties, and increased production costs. Therefore, the molar ratio of silica sol to gel accelerator is controlled to be: 1: (0.2-1.5).
[0043] The present invention also provides a method for preparing the water-transparent and anti-fog porous ceramic, comprising:
[0044] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0045] Step 2: Prepare the green body: inject the slurry into the mold and remove the bubbles in the slurry;
[0046] Step 3, green body drying and demoulding: put the mold in step 2 into a non-air-blasting oven for drying, and take the green body out of the mold after it is dry;
[0047] Step 4, sintering: sintering the taken-out green body in a muffle furnace to obtain water-transparent and anti-fog porous ceramics.
[0048] Specifically, in the above step 2, considering that some oxygen will be dissolved in the slurry and bubbles will be generated during the mixing of the slurry, it may lead to a decrease in the mechanical strength of the later product, increase the refraction and scattering of natural light, and reduce the transparency. Therefore, vacuum degassing, vibration degassing, centrifugal degassing and other methods can be used for degassing.
[0049] Specifically, in the above step 3, considering that the free water inside the product evaporates rapidly when the oven is in the blasting state, many tiny pores may be formed inside the product, resulting in uneven shrinkage, and excessive capillary force may cause the product to crack or deform. Therefore, the oven is controlled to be in the non-blasting state.
[0050] Specifically, in the above step 3, it is considered that too high a drying temperature will generate a larger capillary force, increase shrinkage, and may cause cracking of the product; however, too low a drying temperature will extend the drying cycle and increase production costs. Therefore, the drying temperature is controlled to be 30-80°C and the drying time is 7-23 days.
[0051] Specifically, in the above step 4, the sintering temperature is too high, the surface of the product is over-sintered, a small number of crystals are generated, the internal grain size is uneven, the refraction and scattering are serious, the transmittance is affected, the internal nanopore structure is filled with liquid phase, the sample density increases, and the transparency decreases; however, if the sintering temperature is too low, the sample is not completely sintered, and the porosity is also high, resulting in high scattering and refraction of visible light, low mechanical properties and transparency. At the appropriate sintering temperature, too long a holding time will lead to uneven grain growth, reduced transmittance, and energy waste. Too short a holding time will lead to uneven sintering of the product, and pores or cracks may appear, which will reduce the product quality. Therefore, the sintering temperature is controlled to be 500-800°C and the holding time is 1-3h.
[0052] The preparation method uses the addition of solvents to silica sol to improve the integrity of porous ceramics, increase porosity, shorten gel time, etc., to obtain porous silicon oxide ceramics with adjustable transparency and anti-fog and heat-insulating functions.
[0053] Specifically, the water-transparent and anti-fog type porous silica ceramic of the present invention has a complete structure, a porosity of 45.5% to 50.2%, a transparency of 0.5% to 7% after drying, a transparency of 23% to 42% after firing, a transparency of 55% to 82% after immersion in water, and a compressive strength of 15.3 to 23.7 MPa.
[0054] The water-transparent and anti-fogging silica porous ceramics of the present invention can be used as a highly transparent material comparable to window glass and the like, and can be used as an ideal candidate for a material having heat-insulating and anti-fogging functions in a high-humidity environment.
[0055] Compared with the prior art, the water-transparent and anti-fog type porous silicon oxide ceramics of the present invention use silica sol as raw material, to which solvents such as integrity control agent, porosity enhancer and gel promoter are added, and through reasonable selection and proportioning of these raw materials, the transparency, strength, anti-fog and other properties of the water-transparent and anti-fog type porous ceramics can be controlled and adjusted.
[0056] In the preparation method of the water-transparent and anti-fogging silicon oxide porous ceramics of the present invention, the sintering temperature is low, which greatly reduces the energy consumption.
[0057] In the preparation method of the water-transparent and anti-fogging silicon oxide porous ceramic of the present invention, devitrification of the porous ceramic is avoided by controlling the temperature and time during the sintering process, and finally a structurally complete, water-transparent and anti-fogging silicon oxide porous ceramic is obtained.
[0058] The water-induced transparent and anti-fog type porous silicon oxide ceramics prepared at low temperature by using silica sol and various solvents have the functions of high strength, high porosity and adjustable transparency, and also have the functions of heat insulation and anti-fog, thus realizing the coexistence of the contradictory body of porosity, transparency and strength of the porous ceramics.
[0059] Example 1
[0060] In this embodiment, silica sol is used as the matrix, ethylene glycol is used as the integrity control agent, ammonia water is used as the porosity enhancing agent, and acetonitrile is used as the gel accelerator, wherein the molar ratio of silica sol, integrity control agent, porosity enhancing agent, and gel accelerator is 1:0.8:0.3:0.5.
[0061] The preparation method includes the following steps:
[0062] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0063] Step 2: Prepare the green body: Then inject the slurry into the mold and remove the bubbles in the slurry;
[0064] Step 3, green body drying and demoulding: put the mold in step 2 into a non-air-blasting oven for drying at a temperature of 55°C for 10 to 15 days; after the green body is dried, remove it from the mold;
[0065] Step 4, sintering: sinter the taken-out green body in a muffle furnace at a sintering temperature of 600° C. for 2 hours to obtain water-transparent and anti-fog porous ceramics.
[0066] This embodiment carried out multiple groups of parallel experiments. The water-transparent and anti-fog porous ceramics prepared in this embodiment have a complete structure, a porosity of 45.5% to 48.6%, a transparency of 35% to 42% after firing, a transparency of 76% to 82% after immersion in water, and a compressive strength of 21.3 to 23.7 MPa.
[0067] Example 2
[0068] In this embodiment, silica sol is used as the matrix, dichloromethane is used as the integrity control agent, ammonia water is used as the porosity enhancing agent, and n-hexane is used as the gel accelerator, wherein the molar ratio of silica sol, integrity control agent, porosity enhancing agent, and gel accelerator is 1:0.8:0.3:0.2.
[0069] The preparation method includes the following steps:
[0070] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0071] Step 2: Prepare the green body: Then inject the slurry into the mold and remove the bubbles in the mixed liquid;
[0072] Step 3, green body drying and demoulding: put the mold in step 2 into a non-air-blasting oven for drying at a temperature of 60°C for 10 to 13 days; after the green body is dried, remove it from the mold;
[0073] Step 4, sintering: sintering the taken-out green body in a muffle furnace at a sintering temperature of 600° C. for 2 hours to obtain a water-transparent and anti-fog porous ceramic;
[0074] This embodiment carried out multiple parallel experiments. The water-transparent and anti-fog porous ceramics prepared in this embodiment have a complete structure, a porosity of 46.6% to 50.8%, a transparency of 30% to 36% after firing, a transparency of 70% to 78% after immersion in water, and a compressive strength of 17.1 to 22.2 MPa.
[0075] Example 3
[0076] In this embodiment, silica sol is used as the matrix, ethylene glycol is used as the integrity control agent, acetone is used as the porosity enhancer, and acetonitrile is used as the gel accelerator, wherein the molar ratio of silica sol, integrity control agent, porosity enhancer, and gel accelerator is 1:0.7:0.3:0.7.
[0077] The preparation method includes the following steps:
[0078] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0079] Step 2: Prepare the green body: Then inject the slurry into the mold and remove the bubbles in the slurry;
[0080] Step 3, green body drying and demoulding: put the mold in step 2 into a non-air-blasting oven for drying at a temperature of 50°C for 15 to 21 days, and take the green body out of the mold after it is dried;
[0081] Step 4, sintering: sinter the taken-out green body in a muffle furnace at a sintering temperature of 500° C. for 2 hours to obtain water-transparent and anti-fog porous ceramics.
[0082] This embodiment carried out multiple groups of parallel experiments. The water-transparent and anti-fog porous ceramics prepared in this embodiment have a complete structure, a porosity of 47.2% to 51.7%, a transparency after firing of 28% to 35%, a transparency after immersion in water of 69% to 77%, and a compressive strength of 15.3 to 19.5 MPa.
[0083] Example 4
[0084] In this embodiment, silica sol is used as the matrix, dichloromethane is used as the integrity control agent, acetone is used as the porosity enhancer, and acetonitrile is used as the gel accelerator, wherein the molar ratio of silica sol, integrity control agent, porosity enhancer, and gel accelerator is 1:0.5:0.2:0.5.
[0085] The preparation method includes the following steps:
[0086] Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry;
[0087] Step 2: Prepare the green body: Then inject the slurry into the mold and remove the bubbles in the slurry;
[0088] Step 3, green body drying and demoulding: put the mold in step 2 into a non-air-blasting oven for drying at a temperature of 65°C for 8 to 12 days, and take the green body out of the mold after it is dried;
[0089] Step 4, sintering: sinter the taken-out green body in a muffle furnace at a sintering temperature of 550° C. for 2 hours to obtain water-transparent and anti-fog porous ceramics.
[0090] This embodiment carried out multiple parallel experiments. The water-transparent and anti-fog porous ceramics prepared in this embodiment have a complete structure, a porosity of 46.1% to 50.2%, a transparency after firing of 23% to 32%, a transparency after immersion in water of 55% to 61%, and a compressive strength of 16.3 to 21.8 MPa.
[0091] Comparative Example 1
[0092] Comparative Example 1 discloses a transparent porous ceramic prepared by the same method using the slurry in Example 1, except that:
[0093] In step 3, the mold in step 2 is placed in an oven with air blowing to dry.
[0094] Comparative Example 2
[0095] Comparative Example 2 discloses a transparent porous ceramic prepared by the same method as in Example 1, except that:
[0096] In step 4, the sintering temperature was changed to 900°C and kept at this temperature for 1 hour.
[0097] Comparative Example 3
[0098] Comparative Example 3 discloses a transparent porous ceramic prepared by the same method as in Example 1, except that:
[0099] The molar ratio of silica sol to gel accelerator in step 1 is 1:4.0. The transparency of the ceramic of this comparative example after sintering is 17% to 24%, and the transparency after immersion in water is 46% to 53%.
[0100] Comparative Example 4
[0101] Comparative Example 4 discloses a transparent porous ceramic prepared by the same method as in Example 2, except that:
[0102] In step 3, the mold in step 2 is placed in a non-air-blasting oven for drying, and the drying temperature is changed to 120°C.
[0103] Comparative Example 5
[0104] Comparative Example 5 discloses a transparent porous ceramic prepared by the same method as in Example 4, except that:
[0105] In step 1, no gel accelerator is added to the slurry.
[0106] Comparative Example 6
[0107] Comparative Example 6 discloses a transparent porous ceramic prepared by the same method as in Example 2, except that:
[0108] The molar ratio of silica sol to porosity enhancer in step 1 is 1:5.0. The ceramic of this comparative example breaks into slag during the sintering process.
[0109] The relevant parameter comparison table of Examples 1-4 and Comparative Examples 1-6 is shown in Table 1 below. It can be seen from Table 1 that for transparent porous ceramics prepared using the same ceramic slurry, different sintering temperatures and different material molar ratios have a significant impact on porosity, strength and transmittance.
[0110] The relevant parameter comparison table of Examples 1-4 and Comparative Examples 1-6 is shown in Table 1 below. Figure 1 , Figure 2 The optical image of the water-transparent and anti-fogging porous silicon oxide ceramic obtained in Example 1 of the present invention after drying, sintering and water absorption; Figure 3 This is a scanning electron microscope image of the water-transparent and anti-fog porous ceramic of Example 2 of the present invention; Figure 4 This is an anti-fog diagram of the water-transparent and anti-fog porous ceramic of Example 1 of the present invention; Figure 5 This is a thermal insulation diagram of the water-transparent and anti-fog porous ceramic according to Example 1 of the present invention. Figure 6 This is a schematic diagram of the fragmentation after blast drying of Comparative Example 1 of the present invention. It can be seen that the porous ceramic of the present invention has a complete structure, high strength, good transparency after sintering, high water transparency, anti-fogging and good heat insulation performance.
[0111] Table 1 Data of Examples and Comparative Examples
[0112]
[0113] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A water-transparent and anti-fog porous ceramic, characterized in that: The raw materials of the water-transparent and anti-fog porous ceramics include silica sol, integrity control agent, porosity enhancer and gel accelerator; The integrity control agent includes one or more of propylene oxide, ethylene glycol and methylene chloride; The porosity enhancing agent includes one or more of dimethylformamide, acetone, propionaldehyde and ammonia water; The gel accelerator includes one or more of n-hexane, acetonitrile, methyl formate and cyclohexane; The molar ratio of the silica sol, integrity control agent, porosity enhancer and gel accelerator is 1:(0.3-2.1):(0.05-0.8):(0.2-1.5); The preparation method of the water-transparent and anti-fog porous ceramic comprises: Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry; Step 2: Prepare the green body: inject the slurry into the mold and remove the bubbles in the slurry; Step 3, green body drying and demoulding: put the mold in step 2 into an oven for drying, and take the green body out of the mold after it is dry; Step 4: Sintering: Sintering the taken-out green body to obtain water-transparent and anti-fog porous ceramics.
2. The water-transparent and anti-fog porous ceramic according to claim 1, characterized in that: The molar ratio of the silica sol, the integrity control agent, the porosity enhancer and the gel accelerator is 1:(0.5-2.1):(0.2-0.8):(0.2-1.5).
3. A method for preparing the water-transparent and anti-fog porous ceramic according to claim 1 or 2, characterized in that: include: Step 1, preparing slurry: adding integrity control agent, porosity enhancer and gel accelerator to silica sol respectively and stirring fully until the mixture is evenly mixed to obtain slurry; Step 2: Prepare the green body: inject the slurry into the mold and remove the bubbles in the slurry; Step 3, green body drying and demoulding: put the mold in step 2 into an oven for drying, and take the green body out of the mold after it is dry; Step 4: Sintering: Sintering the taken-out green body to obtain water-transparent and anti-fog porous ceramics.
4. The preparation method according to claim 3, characterized in that: In the step 2, the bubbles in the slurry are removed by vacuum degassing, vibration degassing or centrifugal degassing.
5. The preparation method according to claim 3, characterized in that: In step 3, the oven is controlled to be in a non-blowing state.
6. The preparation method according to claim 3, characterized in that: In step 3, the drying temperature is controlled to be 30-80°C.
7. The preparation method according to any one of claims 3 to 6, characterized in that: In step 4, the sintering temperature is controlled to be 500-800° C. and kept warm for 1-3 hours.
